Centerbook the Center for Advanced Visual Studies and the evolution of art-science-technology at MIT - Goldring-Piene, Elizabeth 1945-; Sebring, Ellen ca. 20. Jh (SA+P Press, School of Architecture + Planning, 2019)
In 1967, in a time of student unrest, the Massachusetts Institute of Technology did the unexpected: it established the first academic center for research and collaboration in art, science, and technology. The Center for Advanced Visual Studies (CAVS) brought artists to the MIT campus with radical expressions of a rapidly evolving technological era. The brainchild of founding director Gyorgy Kepes, CAVS sought to repair the distance between practitioners of art and engineering within the halls of MIT. "The scientist may be an extra brain to the artist, and the engineer may be an extra arm to the artist, whereas the artist can be an extra eye to the scientist and engineer," wrote long-time director Otto Piene in Centerbeam, a 1978 book about CAVS. As a breeder of new art forms and future-oriented artistic education, CAVS became a pioneering model for the art, technology and media labs that proliferated worldwide. This first comprehensive history of CAVS presents an inside view, told through personal accounts, exhibit documentation, and groundbreaking artwork. The book chronicles, in vivid visual narrative and testimony by those who were there, the birth and flowering of a unique research node dedicated to multiple interactions of art, science, technology and environment
Keywords: Massachusetts Institute of Technology; Massachusetts Institute of Technology -- Center for Advanced Visual Studies; Geschichte; Geschichte 1967-2019; Medienkunst; Auswirkung; Kunstbetrieb; Art and science / Massachusetts